2016
DOI: 10.3389/fmars.2016.00021
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Declines in Philippine Fisheries and its Implications to Coastal Municipal Fishers' Catch and Income

Abstract: The problem of overexploitation in global fisheries is well-recognized. However, published assessment of fisheries spatio-temporal trends at the national scale is lacking for many high biodiversity developing countries, which is problematic since fisheries management is often implemented at the local or national levels. Here, we present the long-term spatio-temporal trends of Philippine fisheries production based on the landed national fish catch data and fishers' interviews. We found that the total Philippin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…Caro (2007) recognizes the contribution of descriptive behavioral information in addressing specific conservation challenges. With the dwindling fisheries resources (Anticamara and Go, 2016), understanding fish behavior could aid in the conservation and management of these resources.…”
Section: Local Ecological Knowledgementioning
confidence: 99%
“…Caro (2007) recognizes the contribution of descriptive behavioral information in addressing specific conservation challenges. With the dwindling fisheries resources (Anticamara and Go, 2016), understanding fish behavior could aid in the conservation and management of these resources.…”
Section: Local Ecological Knowledgementioning
confidence: 99%
“…Increasingly since the 1980s, however, fisheries catches have provided limited returns. There is much local variation, but cases of declining or stagnating catches in the face of increased effort are common across the country (Muallil et al 2014;Anticamara and Go 2016). The case study from Ambulong corroborates these national trends, where there do not appear to be many new types of fishing that can be profitably exploited.…”
Section: Historical Trajectoriesmentioning
confidence: 54%
“…The FAO's profile on Philippines fisheries notes that: 'all of the country's main fish species and marine organisms are showing signs of overfishing…' (FAO 2014). A recent national review concluded that 'fish catch has not increased over time (and in fact, has decreased for several provinces), despite continuously increasing fishing effort in the country and the increasing number of registered municipal and commercial fishers in the Philippines… Philippine fisheries production is declining, with the high production volume of the aquaculture sector (i.e., mostly seaweeds) masking the stagnating or declining fish catch of most capture fisheries in recent times' (Anticamara and Go 2016).…”
Section: Fishery Intensificationmentioning
confidence: 99%
“…Those who are more food secure and those who are more water secure are those who can buy food and water more easily. Given the reports of declining catches at a local level in Ambulong (and the widespread occurrence of this at a national level; Anticamara and Go, ), it seems likely that food and water insecurity may become even more challenging in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Examples of ‘coastal grabbing’ related to rapidly escalating coastal land values for tourism development have also placed pressures on marginalised fishing households, who often have no formal land tenure (Fabinyi, ; Cabral and Aliño, ; Dressler, ; Knudsen, ). Overfishing remains prevalent throughout the country (Anticamara and Go, ). And in response to declining fisheries, the government has been expanding forms of maritime governance such as marine protected areas, often reducing access to fishing grounds for fishers, with significant consequential social impacts (Segi, ).…”
Section: Discussionmentioning
confidence: 99%